Modulation of GABAA receptors and of GABAergic synapses by the natural alkaloid gelsemine - Marileo, Ana M.; Gavilán, Javiera; San Martín, Victoria P.; Lara, Cesar O.; Sazo, Anggelo; Muñoz-Montesino, Carola; Castro, Patricio A.; Burgos, Carlos F.; Leiva-Salcedo, Elías; Aguayo, Luis G.; Moraga-Cid, Gustavo; Fuentealba, Jorge; et al. (Frontiers in Molecular Neuroscience, 2023)
The Gelsemium elegans plant preparations have shown beneficial activity against common diseases, including chronic pain and anxiety. Nevertheless, their clinical uses are limited by their toxicity. Gelsemine, one of the most abundant alkaloids in the Gelsemium plants, have replicated these therapeutic and toxic actions in experimental behavioral models. However, the molecular targets underlying these biological effects remain unclear. The behavioral activity profile of gelsemine suggests the involvement of GABAA receptors (GABAARs), which are the main biological targets of benzodiazepines (BDZs), a group of drugs with anxiolytic, hypnotic, and analgesic properties. Here, we aim to define the modulation of GABAARs by gelsemine, with a special focus on the subtypes involved in the BDZ actions. The gelsemine actions were determined by electrophysiological recordings of recombinant GABAARs expressed in HEK293 cells, and of native receptors in cortical neurons. Gelsemine inhibited the agonist-evoked currents of recombinant and native receptors. The functional inhibition was not associated with the BDZ binding site. We determined in addition that gelsemine diminished the frequency of GABAergic synaptic events, likely through a presynaptic modulation. Our findings establish gelsemine as a negative modulator of GABAARs and of GABAergic synaptic function. These pharmacological features discard direct anxiolytic or analgesic actions of gelsemine through GABAARs but support a role of GABAARs on the alkaloid induced toxicity. On the other hand, the presynaptic effects of the alkaloid provide an additional mechanism to explain their beneficial effects. Collectively, our results contribute novel information to improve understanding of gelsemine actions in the mammalian nervous system.